Penggunaan Azotobacter dan Kompos Kulit Buah Kakao Terhadap Pertumbuhan dan Efisiensi Penggunaan Nitrogen Pada Pembibitan Utama Kelapa Sawit - Wilda Lumban Tobing; Mariani Sembiring (Agrosains : Jurnal Penelitian Agronomi, 2021)
The expansion of oil palm plantations continues to increase so that it requires quality seed. Nurseries need to be done before moving to the field. The use of Azotobacter and cocoa fruit skin compost is one way to increase the  growth and nitrogen use efficiency in oil palm in main nursery. This research was aimed to know the growth and nitrogen use efficiency of palm oil in main nursery. This research was conducted on the research area of the Agricultural Agribusiness College of Agriculture Practices (STIPAP) Medan and the Laboratory of Balai Pengkajian Teknologi Pertanian (BPTP) of North Sumatra and the Agricultural Laboratory of the University of North Sumatera from February until Juli 2013. The method used was Randomized Group Design factorial with 3 replications and followed by Duncan test at α=5%. The first factor is Azotobacter including without giving Azotobacter (A0), 20 ml/polybag (A1) and 40 ml/polybag (A2). The second factor is cocoa fruit skin compost, which consists of 3 of them, namely without compost (K0), 125 g/polybag (K1), and 250 g/polybag (K2). The research parameters were plant dry weight (g), nitrogen uptake (mg) and N use efficiency (EPN). The results showed that the use of Azotobacter and cocoa fruit skin compost were able to significantly increasing dry weight of plant and N uptake of oil palm seeds and gave the highest EPN value of 12.93.